Heat Transfer in a Pulsed Fluidized Bed of Biomass Particles - Jia, Dening; Bi, Xiaotao; Lim, C. Jim; Sokhansanj, Shahab; Tsutsumi, Atsushi (Industrial & engineering chemistry research, 2017)
Bed-to-surface heat transfer coefficients of various biomass particles were measured in a pulsed fluidized bed. Effects of flow rate, pulsation frequency, particle size distribution, fines, and vibration on heat transfer were investigated. Higher gas flow rates generally yielded higher heat transfer coefficients. Natural frequency was found to be optimum as it offered ample bed movement and internal solid circulation without too much inactivity between pulsation cycles. Heat transfer was also heavily influenced by the interaction between gas convective and particle convective heat transfer, which was verified by the proposed heat transfer model. Two mechanisms, one of which treated the flow-on and flow-off period within a pulsation cycle individually, the other utilized the actual bubble rise velocity obtained via high-speed imaging were identified to account for the significantly different flow behavior below and above natural frequency. Good agreement was observed between experimental data and modeled results.